Characterization of Functional Groups and Sunscreen Activity of Ethanol Extract of Breadfruit Leaves (Artocarpus altilis) - Gharsina Yumni; Elda Septiana (LPPM Universitas Abdurrab, 2026)
Breadfruit leaves (Artocarpus altilis) contain phenolic and flavonoid compounds with potential as sunscreens. This study aimed to characterize functional groups and determine the in vitro sunscreen activity of the 96% ethanol extract of breadfruit leaves from Tengaran. The extract was obtained by maceration using 96% ethanol. Functional group analysis was performed using FTIR spectroscopy. Sunscreen activity was tested at concentrations of 200, 400, 600, 800, and 1000 ppm using UV-Vis spectrophotometry (290-320 nm), and SPF values were calculated using the Mansur equation. FTIR results indicated the presence of phenolic and flavonoid compounds characterized by functional groups O-H, C-H aliphatic, C=O, C=C aromatic, C=C alkene, NO₂, and C-O. The SPF values obtained were 24.096; 29.474; 32.449; 38.301; and 40.008, respectively, all falling into the ultra-protection category (>15). In conclusion, the extract contains phenolic and flavonoid functional groups and exhibits potent sunscreen activity with ultra protection.